Insights into the effects of cadmium stress on endophytic bacterial community in the hyperaccumulating plant ryegrass. Issue 1 (1st January 2021) - Liang, Shengxian; Zhang, Yue; Cui, Bingjian
ABSTRACT: We investigated the endophytic bacterial community of ryegrass under Cd stress. Results showed ryegrass could tolerate relatively high concentrations of Cd. The fresh weight and shoot length were not significantly affected, while physicochemical parameters, including total nitrogen (TN), total phosphorus (TP), soluble protein (SP), Ca, and Mg, were changed. Exposure to Cd disturbed the composition of endophytes at both phylum and genus levels. Pseudomonas accounted for relatively high proportion, was increased under Cd stress. Additionally, correlation analysis identified that physicochemical parameters, such as TP, TN, Ca and Mg, significantly affected the abundance and composition of endophytic bacterial genera, suggesting these parameters had potential roles in regulation of endophytic microbial communities. In summary, our study investigated the endophytic bacterial community of ryegrass, and characterized its response to Cd stress. These results may shed light on the process of improving the remediation of Cd by modulating endophyte community.